KONTRIBUSI MEDIA KARTU KATA DALAM MENUNJANG KEMAMPUAN MEMBACA PERMULAAN KELAS I SDN KEBOAN ANOM - Damayanti Silaban, Hanatasya; Achmad Fanani; Cholifah Tur Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of students' ability in reading, including students' ability to read the beginning in learning Indonesian language material. Teachers need learning media, one of which is word cards, to help deliver learning materials. The purpose of this researcher is to determine the effect of the application of the synthetic analytical structural method assisted by word card media on the ability to read the beginning. This study uses a quantitative approach. The IBM SPSS 25 program is used to conduct normality tests, homogeneity tests, and t-tests. The results of the study showed the Independent Sample t Test, with a significance value of sig. <0.05 which indicates that there is an effect of the application of the synthetic analytical structural method assisted by word card media on the ability to read the beginning.